1983
DOI: 10.1083/jcb.96.4.1064
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Chinese hamster ovary cells pleiotropically defective in receptor-mediated endocytosis.

Abstract: Populations of Chinese hamster ovary cells selected for resistance to diphtheria toxin were found to be highly enriched for mutants deficient in the uptake of lysosomal hydrolases via the mannose 6-phosphate receptor. One doubly defective mutant, DTF 1-5-1, exhibited increased resistance to Sindbis virus, although it was able to bind and internalize virus normally. Normal production of virus was obtained when, subsequent to virus binding, the mutant was exposed for 2 rain to acidic pH. Similarly, a shift to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
86
2

Year Published

1984
1984
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 46 publications
7
86
2
Order By: Relevance
“…This is consistent with penetration occurring from large endosomes. The resistance of the mutant cell lines to enveloped viruses (27,28) would appear to be in conflict with our finding that many of the large endosomes in the mutants have a pH <6.2. However, studies of the kinetics of Semliki Forest virus uncoating and penetration have shown that these processes are very similar in the mutants and wild-type cells (Marsh, M., A. Helenius, and I. Mellman, personal communication).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This is consistent with penetration occurring from large endosomes. The resistance of the mutant cell lines to enveloped viruses (27,28) would appear to be in conflict with our finding that many of the large endosomes in the mutants have a pH <6.2. However, studies of the kinetics of Semliki Forest virus uncoating and penetration have shown that these processes are very similar in the mutants and wild-type cells (Marsh, M., A. Helenius, and I. Mellman, personal communication).…”
Section: Discussioncontrasting
confidence: 55%
“…3). We speculate that the higher pH large endosomes are the sorting endosomes; this would be consistent with the inefficiency of the cells in releasing iron from "IT (13,40) and in delivering endocytosed lysosomal enzymes to lysosomes (27,28). Based on this we assign a pH >6.2 to the sorting endosomes and a pH of 5.2-6.0 to the late prelysosomal endosomes in the mutants.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Several groups have obtained CHO mutants pleiotropically defective in endocytosis by selecting cells that were resistant to diphtheria toxin (2,9,14,21). These mutants are also resistant to other toxins and certain viruses that require an acidic pH for toxicity or infectivity.…”
mentioning
confidence: 99%